THE EFFECT OF INTERET INTEREST RATES AND SERVICE QUALITY ON CUSTOMER SAVING DECISIONS AT BANK BRI - Muh. Rezky Naim (Yayasan Nuraini Ibrahim Mandiri, 2025)
The aim of this research is to determine the influence of interest rates and service quality on customers' decisions to save at Bank BRI Topoyo Unit, Central Mamuju Regency. This research uses quantitative methods by collecting data through questionnaires. This research was carried out at Bank BRI Topoyo Unit, Central Mamuju Regency with a sample size of 96 customers. Questionnaire data were analyzed with the help of the SPSS program. The results of the research show that interest rates have a significant effect on customers' decisions to save at Bank BRI Topoyo Unit, Central Mamuju Regency, service quality has a significant effect on customers' decisions to save at Bank BRI Topoyo Unit, Central Mamuju Regency and interest rates and service quality have a significant effect simultaneously on customer's decision to save at Bank BRI Topoyo Unit, Central Mamuju Regency. Keywords: Interest Rates, Service Quality, Saving Decisions